Intratumor heterogeneity of prognostic DNA-based molecular markers in adrenocortical carcinoma. Issue 7 (July 2020) - Jouinot, Anne; Lippert, Juliane; Fassnacht, Martin; de La Villeon, Bruno; Septier, Amandine; Neou, Mario; Perlemoine, Karine; Appenzeller, Silke; Sibony, Mathilde; Gaujoux, Sébastien; Dousset, Bertrand; Libe, Rossella; et al.
Abstract : Background: : The prognosis of adrenocortical carcinoma (ACC) is heterogeneous. Genomic studies have identified ACC subgroups characterized by specific molecular alterations, including features measured at DNA level (somatic mutations, chromosome alterations, DNA methylation), which are closely associated with outcome. The aim of this study was to evaluate intratumor heterogeneity of prognostic molecular markers at the DNA level. Methods: : Two different tissue samples (primary tumor, local recurrence or metastasis) were analyzed in 26 patients who underwent surgery for primary or recurrent ACC. DNA-related biomarkers with prognostic role were investigated in frozen and paraffin-embedded samples. Somatic mutations of p53/Rb and Wnt/β-catenin pathways were assessed using next-generation sequencing ( n  = 26), chromosome alteration profiles were determined using SNP arrays ( n  = 14) and methylation profiles were determined using four-gene bisulfite pyrosequencing ( n  = 12). Results: : Somatic mutations for ZNRF3, TP53, CTNN1B and CDKN2A were found in 7, 6, 6 and 4 patients, respectively, with intratumor heterogeneity in 8/26 patients (31%). Chromosome alteration profiles were 'Noisy' (numerous and anarchic alterations) in 8/14 and 'Chromosomal' (extended patterns of loss of heterozygosity) in 5/14 of the study samples. For these profiles, no intratumor heterogeneity was observed. Methylation profiles were hypermethylated in 5/12 and non-hypermethylated in 7/12 of the study samples. Intratumor heterogeneity of methylation profiles was observed in 2/12 patients (17%). Conclusions: : Intratumor heterogeneity impacts DNA-related molecular markers. While somatic mutation can differ, prognostic DNA methylation and chromosome alteration profile seem rather stable and might be more robust for the prognostic assessment.